2011
DOI: 10.1017/s0003055411000013
|View full text |Cite
|
Sign up to set email alerts
|

Divide and Conquer or Divide and Concede: How Do States Respond to Internally Divided Separatists?

Abstract: W hy do states make concessions to some self-determination movements but not others? This article explores the role of the internal characteristics of these movements, demonstrating that their internal structures play a major role in determining which groups get concessions. Using new data on the structure of self-determination movements and the concessions they receive, I evaluate whether states respond to internally divided movements by trying to "divide and conquer" or "divide and concede." Consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(123 citation statements)
references
References 45 publications
(68 reference statements)
2
121
0
Order By: Relevance
“…Third, deterrence is less effective as retaliation might destabilise the entire system. As a result, groups may be tempted to 'free-ride' and not genuinely cooperate, which could make a relapse more likely (Oye, 1985;Doyle and Sambanis, 2000;Cunningham, 2011).…”
Section: Number Of Factionsmentioning
confidence: 99%
“…Third, deterrence is less effective as retaliation might destabilise the entire system. As a result, groups may be tempted to 'free-ride' and not genuinely cooperate, which could make a relapse more likely (Oye, 1985;Doyle and Sambanis, 2000;Cunningham, 2011).…”
Section: Number Of Factionsmentioning
confidence: 99%
“…1 Since the rebels have a low-variance understanding of the leader's policies, and those policies drove them to war, the rebels are unlikely to believe promises of concessions from the leader (e.g. Cunningham, 2011). It is this commitment problem that leads to a longer civil war (e.g.…”
Section: Leadership Tenure and The Duration Of Civil Warsmentioning
confidence: 99%
“…A number of case studies have empirically explored possible causes for splintering. Several studies have found that competition among rebels, particularly when competing for the "affection" of a particular ethnic group, may encourage outbidding in extremism and in the level of violence (Bloom 2005, Pearlman 2008/2009, Cunningham 2011, Cunningham, Bakke and Seymour. 2012, and Lilja 2012.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When rebels cooperate, the number of political acts produced is controlled and restricted, thus leaving space for productive activity (Tullock, 1974and Collier and Hoeffler, 1998. However, if rebels splinter, competitive pressure increases the number of political acts produced at the expense of productive acts (Bloom 2005, Cunningham 2011, Cunningham et. al.…”
Section: Introductionmentioning
confidence: 99%